Human Resource Training and Planning for Work Productivity of Employees Ministry of Coordinating Ministry of Human Development and Culture - Moh Bonnario; Harries Madiistriyatno; Azis Zulfikar (Eduvest - Journal of Universal Studies, 2021)
The training is intended to improve the mastery of various skills and techniques for carrying out certain, detailed and routine work. Human resource planning serves to determine the number and types of employees needed to achieve the goals that have been set. Work productivity is a comparison between the results achieved (output) with the overall resources (inputs) used per unit of time. The purpose of this study was to determine: The Effect of Training and Human Resource Planning on Employee Work Productivity at the Coordinating Ministry for Human Development and Culture. The sampling technique used in this study the author uses the Random Sampling technique or by using the Slovin formula in Husein Umar. Where each population has the same opportunity to be selected as a sample in this study. The results obtained that partially and simultaneously there is a positive and significant influence between Training and Human Resource Planning on Employee Work Productivity.